Strategi Efektif Pembelajaran Pendidikan Agama Islam di Era Digital - St. Maryam (FKIP UNSULTRA, 2026)
This research aims to examine effective strategies for teaching Islamic Religious Education (PAI) in the digital era through a literature review approach. Developments in information and communication technology have brought significant changes to the world of education, including in Islamic Religious Education (PAI) learning methods and media. The main challenge faced is how to integrate Islamic values ​​with the optimal use of digital technology without compromising the essence of spiritual and moral learning. The method used in this research is a literature review, reviewing various sources such as scientific journals, books, and relevant research reports from the past 10 years. The results of the study indicate several effective strategies that can be implemented, including the use of interactive digital media, the use of online learning platforms, strengthening digital literacy based on Islamic values, project-based learning approaches, and improving teacher competency in educational technology. These strategies have been proven to increase student engagement, material understanding, and the internalization of Islamic values ​​in everyday life. Therefore, Islamic Religious Education (PAI) learning in the digital era requires continuous innovation to remain relevant and able to meet the challenges of the times. This research is expected to serve as a reference for educators in developing adaptive and effective PAI learning in the digital era.